Growth of Corporate Tax in India: An Analysis - Kaur, Gurpreet; Rani, Vaneeta (Gyan Management Journal, 2021)
The direct tax contributes as a major source to the total tax revenue of the government. The biggest component of the direct tax, as well as total tax revenue of the government, is the Corporate Tax as it contributes around 1/3rd of the gross tax revenue of the government. So, it is very important to study the concept of corporate tax, growth in corporate tax revenue, growth in corporate assessees known as tax base, and the corporate tax to gross domestic product (GDP) relationship. The present study throws light on the growth perspective of corporate tax revenue and growth of corporate assessees in India. The corporate tax buoyancy has also been discussed in the paper to know the responsiveness of corporate tax revenue in comparison to the (GDP) of the country. The study has covered the period of 18 years from 2001-02 to 2018. The data has been taken from economic survey reports and the official websites of Income Tax, and Comptroller and Auditor General of India. The analyses of collected data have been carried out by using percentage, simple growth rate and compound annual growth rate.